Kaposi’s sarcoma-associated herpesvirus ORF57 in viral RNA processing - Majerciak, Vladimir (2009)
Kaposi’s sarcoma-associated herpesvirus (KSHV) ORF57 (MTA, mRNA transcript accumulation) is a multifunctional regulator of the expression of viral lytic genes. KSHV ORF57 is expressed during viral lytic infection and is essential for virus production. Like its homologues in the herpesvirus family, ORF57 promotes the accumulation (stabilization) and export of viral intronless RNA transcripts by a mechanism which remains to be defined. The ORF57-Aly/REF interaction plays only a small role in viral RNA export. Although other members of the family generally inhibit the splicing of cellular RNAs, KSHV ORF57 and EBV EB2, in sharp contrast, stimulate viral RNA splicing for the expression of viral intron-containing genes. The functions of KSHV ORF57 are independent of transcription and of other viral proteins; instead, these functions always rely on cellular components and occur in various protein-RNA complexes. ORF57 may synergize with KSHV ORF50 to transactivate a subset of viral promoters by an unknown mechanism. Thus, some functions of ORF57 have been conserved while others have diverged from its homologues as ORF57 adapted over evolution to KSHV biology and pathogenesis.